Estimation of inflammation by Doppler ultrasound: quantitative changes after intra-articular treatment in rheumatoid arthritis. Issue 11 (28th October 2003) - Terslev, L; Torp-Pedersen, S; Qvistgaard, E; Danneskiold-Samsoe, B; Bliddal, H
Abstract : Objective: To evaluate the use of ultrasound, including quantitative Doppler analysis of synovial vascularisation, before and after intra-articular treatment with glucocorticosteroids in patients with rheumatoid arthritis (RA). Methods: 51 patients with RA were followed prospectively after an intra-articular glucocorticosteroid injection. Disease modifying antirheumatic drug treatment was kept unchanged and no further injections given in this observation period. At baseline, disease activity was estimated clinically by target join pain on a 100 mm visual analogue scale, on which the target joint was scored 0–3 for swelling and tenderness, and by ultrasound measurements of grey scale pixels, colour Doppler pixels, and the spectral Doppler resistive index (RI) as indicators of synovial swelling and inflammation. After four weeks, the measurements were repeated on the same joint. An observer unaware of the sequence and patient number evaluated the ultrasound images. Results: At one month follow up after the glucocorticosteroid injection, a marked decrease in the fraction of colour pixels was seen in 41/51 patients (Student's t test p<0.001). Correspondingly, the RI increased indicating a diminished flow to the synovium (Student's t test p<0.01). Both the fraction of colour pixels and the RI values corresponded with the clinical evaluation and with the subjective effect of the treatment. The synovial membrane volume estimated by total amount of pixels showed a significant decrease by 31% after treatment. Conclusion: Ultrasound-Doppler seems to be a promising tool for the estimation of synovial activity in arthritis. After intra-articular glucocorticosteroid, changes in RI and fraction of colour pixels may both be used as quantitative measurements of the blood flow.